Proyecto para la creación e instalación de una microempresa manufacturera textil especializada en la línea de hogar, en la Parroquia de Conocoto, Cantón Quito, Provincia de Pichincha - López Utreras, Andrea Paola (2010)
This work has as main objective to analyze the textile sector has been considered a strategic sector within the imdustria of Ecuador also generated several places direct employment in the country, becoming the second manofacturero sector employs more labor , after the food, beverages and tobacco sector.